2004
DOI: 10.1507/endocrj.51.425
|View full text |Cite
|
Sign up to set email alerts
|

Endocrinological and Pathological Effects of Anabolic-androgenic Steroid in Male Rats

Abstract: Abstract. Many athletes use drugs, especially anabolic androgenic steroids (AAS), but there are few reports on the endocrinological and pathological changes in AAS abusers. In this study we reported the results of endocrinological examinations in rats administered AAS and also physical changes. We separated 37 male Wistar rats (7 weeks old) into 3 groups: Group A was medicated with nandrolone decanoate, metenolone acetate, and dromostanolone; Group B with nandrolone decanoate and saline; and Group C was given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
49
1
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 42 publications
15
49
1
9
Order By: Relevance
“…They speculated that both endogenous and exogenous testosterone or testosterone like substances were measured. (22,38) On the other hand, other study reported that low testosterone level was observed throughout AAS treatment due to negative feedback mechanism with reduced endogenous testosterone secretion. (39) Increased serum testosterone levels than control was also detected in exercise-trained group but less than those levels found in steroid and trained plus steroid groups.…”
Section: Discussionmentioning
confidence: 99%
“…They speculated that both endogenous and exogenous testosterone or testosterone like substances were measured. (22,38) On the other hand, other study reported that low testosterone level was observed throughout AAS treatment due to negative feedback mechanism with reduced endogenous testosterone secretion. (39) Increased serum testosterone levels than control was also detected in exercise-trained group but less than those levels found in steroid and trained plus steroid groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies report normal glucose metabolism when high anabolic-androgenic steroids doses are used in rats. Thus, the effect of high doses of anabolic-androgenic steroids on glucose metabolism remains controversial (Hislop et al 1999, Takahashi et al 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, treatment with relatively high doses of nandrolone leads into decrease of sperm number, sperm motility and change of its morphology. 23 Our results showed significant decrease in sperm concentration which could be due to the exposure to AAS which have effects on the interruption in normal testosterone production which might cause disturbance in regulation of spermatogenesis and eventually leads to decrease in sperm count. 24,25 Other reasons for diminution of sperm concentration may be due to the apoptosis of germ cells, disarranged intratubular cells, destruction of the seminiferous tubules, these demonstrated by AlDomery 20 who examined a histological section of rat testes.…”
Section: Discussionmentioning
confidence: 61%